Effects of multiphase gas and projection on X-ray observables in simulated galaxy clusters as seen by eROSITA - Zuhone, J.; Bahar, Y. E.; Biffi, V.; Dolag, K.; Sanders, J.; Bulbul, E.; Liu, T.; Dauser, Thomas; König, Ole; Zhang, X.; Ghirardini, V. (Astronomy & Astrophysics, 2023)
Context. Galaxy clusters are the most massive bound objects in the recent history of the universe; the number density of galaxy clusters as a function of mass and redshift is a sensitive function of the cosmological parameters. To use clusters for cosmological parameter studies, it is necessary to determine their masses as accurately as possible, which is typically done via scaling relations between mass and observables. Aims. X-ray observables can be biased by a number of effects, including multiphase gas and projection effects, especially in the case where cluster temperatures and luminosities are estimated from single-model fits to all of the emission with an overdensity radius such as r500c. Using simulated galaxy clusters from a realistic cosmological simulation, our aim is to determine the importance of these biases in the context of Spectrum-Roentgen-Gamma/eROSITA observations of clusters. Methods. We extracted clusters from the Box2_hr simulation from the Magneticum suite, and simulated synthetic eROSITA observations of these clusters using PHOX to generate the photons and the end-to-end simulator SIXTE to trace them through the optics and simulate the detection process. We fitted the spectra from these observations and compared the fitted temperatures and luminosities to the quantities derived from the simulations. We fitted an intrinsically scattered LX - T scaling relation to these measurements following a Bayesian approach with which we fully took into account the selection effects and the mass function. Results. The largest biases on the estimated temperature and luminosities of the clusters come from the inadequacy of single-temperature model fits to represent emission from multiphase gas, and from a bias arising from cluster emission within the projected r500c along the line of sight but outside of the spherical r500c. We find that the biases on temperature and luminosity due to the projection of emission from other clusters within r500c is comparatively small. We find eROSITA-like measurements of Magneticum clusters following a LX - T scaling relation that has a broadly consistent but slightly shallower slope compared to the literature values. We also find that the intrinsic scatter of LX at given T is lower compared to the recent observational results where the selection effects are fully considered.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Galaxies: clusters: intracluster medium; Methods: numerical; X-rays: galaxies: clusters